L’agonie de Raimundo, fils d’Unamuno, et le sentiment comique de la vie - Yves Roullière (Cahiers de Civilisation Espagnole Contemporaine)
There is probably no greater shock for parents than to see one of their children doomed to a slow and no less premature death. Miguel de Unamuno suffered the same fate in 1896 with his third child, Raimundo Jenaro, whose hydrocephalus became apparent in the first few months of his life and whose condition worsened until his death at the age of almost seven. Unamuno made enormous use of his personal life, going so far as to make his family experience one of the main criteria for assessing the relevance of any given assertion. The case of Raimundo is no exception to the rule, but it remains a blind spot for the overwhelming majority of commentators, who have preferred or not dared to point out its major impact on his work. In contrast, this study will attempt to show that Raimundo's traumatic and hard existence had a decisive influence on the main aspects of Unamuno's work: philosophical, mystical, poetic and fictional, particularly in his approach to tragedy and comedy, sentiment and love.